Intangible Delicacies: Production and Embarrassment in International Settings - Herzfeld, Michael (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
The intention of the author of this article is to worry away at the limits of the concept of intangible culture. In pursuing this line of critique, he wonders how an international organization such as UNESCO, which is not only composed of nation-states but depends on their cooperation to get its work done, can address the status of cultural practices that are central to national self-recognition but that these nation-states do not want to admit to each other. These are the practices that he associates with the concept of “cultural intimacy” – the “dirty laundry” that every nation-state confronts, denies, and yet, for the most part, guiltily enjoys. The space of cultural intimacy includes all those aspects of cultural and social life that are locally recognized but externally suppressed. In virtually every country, there are deeply embedded and widely popular practices that do not seem to conform to a largely Western-inspired and globally dominant canon of respectability. These practices arguably represent the most intractable challenge to formal, state-led representations of culture.